The effects of betalain-rich cacti (dragon fruit and cactus pear) on endothelial and vascular function: a systematic review of animal and human studies. Issue 8 (27th July 2020) - Cheok, Alex; George, Trevor W.; Rodriguez-Mateos, Ana; Caton, Paul W.
Abstract : This systematic review assesses the evidence for the effects of edible cacti (dragon fruit and cactus pear) on vascular and endothelial function based on animal models and human studies. Abstract : Dragon fruit ( Hylocereus ) and cactus pear ( Opuntia ) are cacti species that have been widely used globally as a reliable source of food as well as traditional folk remedies. They have become of scientific interest recently due to their high levels of bioactive phytochemical compounds, in particular betalains. Earlier systematic reviews have explored the impact of supplementation of these cactus species on obesity, type-2 diabetes mellitus and cardiovascular risk factors: body weight and composition, serum triglycerides, cholesterol, blood glucose and blood pressure. However, effects on vascular health and endothelial function have yet to be reviewed. In order to address this gap in the literature, a systematic review has been conducted to evaluate the physiological effects of Hylocereus and Opuntia cacti on endothelial and vascular function in in vivo animal models and human studies. An electronic search was performed in the following databases: PubMed (MEDLINE), EMBASE ( via Ovid), CINAHL, Scopus, Web of Science®, and The Cochrane Library (CENTRAL). All journals were searched since inceptions up to January 2020 without language restriction. Outcomes of interest were blood pressure, arterial stiffness, vascular reactivity and biochemical markers of endothelial dysfunction. Two investigators independently performed the study selection and data extraction. From 394 references, only 16 studies (9 animal and 7 human) fulfilled the eligibility criteria. Animal studies suggested a potential increase in vasodilation and serum nitric oxide and a reduction in vascular stiffness and blood pressure. The small number of human studies showed a reduction in heart rate as well as an increase in heart rate variability. Although these findings appear to indicate improvement in vascular health, there is a severe lack of robust, randomised human intervention studies to identify underlying mechanisms, optimal dose and long-term effects of cacti consumption.